Author Correction: Rare genetic variants affecting urine metabolite levels link population variation to inborn errors of metabolism (Nature Communications, (2021), 12, 1, (964), 10.1038/s41467-020-20877-8) - Cheng, Yurong; Schlosser, Pascal; Hertel, Johannes; Sekula, Peggy; Spiekerkoetter, Ute; Mielke, Johanna; Freitag, Daniel F.; Schmidts, Miriam; Oefner, Peter J.; Kronenberg, Florian; Eckardt, Kai-Uwe; Thiele, Ines; et al. (Nature Communications, 2021)
The original version of the Supplementary Data associated with this Article included two incorrect column labels in Supplementary Data 3 and 6 files. All numeric content remains unchanged. The HTML has been updated to include a corrected version of Supplementary Data 3 and 6; the original version of Supplementary Data 3 and 6 with the incorrectly labelled column headers can be found as Supplementary Information associated with this Correction.
CRIS-Team Scopus Importer:2021-10-22